Uji Kevalidan dan Kepraktisan E-Modul Matematika Berbasis Flipbook - Adam, Maryam; Abbas, Nurhayati; Badu, Syamsu Qamar (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
This study aims to determine the development procedure and produce valid and practical mathematical e-modules on rectangular, square and triangular material. The type of research used is Research and Development (RnD) research with the development model used is the PLOMP model with four stages. The research subjects were students of class VIII SMP Negeri 1 Kwandang. The results showed that the validator's assessment of the mathematics e-module obtained the validity criteria and was declared very suitable for use in the learning process. The use of e-mathematical modules gets positive responses from teachers with an average percentage of 85.37% and positive responses from students with an average percentage of 78.6%. The average percentage of teacher and student responses is in the very good category, so that the module is said to meet the practical criteria. Based on the results of the study it can be concluded that the e-module mathematics material for rectangles, squares and triangles fulfills valid and practical aspects so that it is suitable for use in learning at SMP Negeri 1 Kwandang.